Genome-Wide Sequencing Reveals Two Major Sub-Lineages in the Genetically Monomorphic Pathogen Xanthomonas Campestris Pathovar Musacearum. - Wasukira, Arthur; Tayebwa, Johnbosco; Thwaites, Richard; Paszkiewicz, Konrad; Aritua, Valente; Kubiriba, Jerome; Smith, Julian; Grant, Murray; Studholme, David J. (Genes, 2012)
The bacterium Xanthomonas campestris pathovar musacearum (Xcm) is the causal agent of banana Xanthomonas wilt (BXW). This disease has devastated economies based on banana and plantain crops (Musa species) in East Africa. Here we use genome-wide sequencing to discover a set of single-nucleotide polymorphisms (SNPs) among East African isolates of Xcm. These SNPs have potential as molecular markers for phylogeographic studies of the epidemiology and spread of the pathogen. Our analysis reveals two major sub-lineages of the pathogen, suggesting that the current outbreaks of BXW on Musa species in the region may have more than one introductory event, perhaps from Ethiopia. Also, based on comparisons of genome-wide sequence data from multiple isolates of Xcm and multiple strains of X. vasicola pathovar vasculorum, we identify genes specific to Xcm that could be used to specifically detect Xcm by PCR-based methods.
Keywords: Banana Xanthomonas wilt; Whole-genome sequencing; SNP; Molecular markers; Ensete ventricosum; Xanthomonas vasicola